Etiology and outcomes of current posterior chamber phakic intraocular lens extraction - Hayakawa, Hideki (Sci Rep, 2020)
This study was aimed to review the etiology and the outcomes of current posterior chamber phakic intraocular lens (Visian ICL, STAAR Surgical) extraction. This review comprised 770 eyes of 403 consecutive patients undergoing ICL extraction. We evaluated prevalence, etiology, uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), predictability, and patient satisfaction. ICL extraction was required in 8 of 770 (1.0%) eyes. The most common reason was the progression of the pre-existing cataract formation in 5 eyes (63%), followed by residual refractive errors in 3 eyes (38%). Of the 7 eyes targeted for emmetropia, 7 (100%) and 6 (86%) achieved UDVAs of 20/40 and 20/20 or better, respectively. Three eyes (38%) showed no change in CDVA, 3 eyes (38%) gained 1 line, 2 eyes (25%) gained 3 or more lines. 88% and 100% were within ± 0.5 and 1.0 diopter (D), respectively, of the targeted correction. Patient satisfaction improved significantly, from 3.0 ± 1.4 preoperatively, to 8.0 ± 2.4 postoperatively. No vision-threatening complications occurred. ICL extraction was required in approximately 1% of ICL-implanted eyes. Visual and refractive outcomes were good, and patient satisfaction was overall high, even in ICL-extracted eyes.